A longitudinal view of factors that influence the emotional well-being of family caregivers to individuals with heart failure. (3rd August 2017) - Grigorovich, Alisa; Lee, Adrienne; Ross, Heather; Woodend, A. Kirsten; Forde, Samantha; Cameron, Jill I.
ABSTRACT: Objectives : Caring for community-residing patients with heart failure can affect caregivers' emotional wellbeing. However, few studies have examined caregivers' well-being longitudinally, or identified factors associated with positive and negative outcomes. The objective of this longitudinal cohort study was to examine changes in caregivers' well-being over time, and to identify patient and caregiver factors associated with positive and negative outcomes. Method: Fifty caregiver/heart failure patient dyads were recruited from an acute care facility and followed in the community. All participants completed surveys at hospital admission and 3, 6 and 12 months later. Caregivers completed assessments of depression symptoms and positive affect and standardized measures to capture assistance provided, mastery, personal gain, social support, participation restriction, and patients' behavioral and psychological symptoms. From patients, we collected demographic characteristics and health-related quality of life. Individual Growth Curve modelling was used to analyze the data. Results : Caregivers' negative and positive emotions remained stable over time. Depression symptoms were associated with higher participation restriction in caregivers. Positive affect was associated with more personal gain and more social support. Patients' health-related quality of life and their behavioral and psychological symptoms were not significantly associated with caregivers' emotional outcomes. Conclusion: Interventions should be offered based on caregivers' needs rather than patients' health outcomes, and should focus on fostering caregivers' feelings of personal gain, assisting them with securing social support, and engaging in valued activities.